2018
DOI: 10.2196/preprints.10754
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine Learning for Predicting Adherence to Internet-Delivered Psychotherapy for Symptoms of Depression and Anxiety after Myocardial Infarction: Insights from the U-CARE Heart Trial (Preprint)

Abstract: BACKGROUND BACKGROUND: Low adherence to recommended treatments is a multifactorial problem in rehabilitation for patients with myocardial infarction (MI). In a nationwide trial of internet-delivered cognitive behavior therapy (iCBT) for the high-risk subgroup of patients with MI also reporting symptoms of anxiety, depression, or both (MI-ANXDEP), adherence was low. Since low adherence to psychotherapy leads to a waste of therapeutic resources and risky treatment abortion in MI-ANXDEP pa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The identified studies (n=29) were mostly conducted in the USA (n=10), Sweden (n=6), and the UK (n=6). The studies included a diverse sample of adults (n=22), college students and young adults (n=4), anonymous users (n=2), and adolescents (n=1) ( 28 33 , 41 , 73 94 ). Eight studies reported on the ethnicity of the participants ( 30 , 32 , 41 , 74 , 76 , 77 , 80 , 83 ), and in most of the studies between 31% and 91% of the participants identified as White.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The identified studies (n=29) were mostly conducted in the USA (n=10), Sweden (n=6), and the UK (n=6). The studies included a diverse sample of adults (n=22), college students and young adults (n=4), anonymous users (n=2), and adolescents (n=1) ( 28 33 , 41 , 73 94 ). Eight studies reported on the ethnicity of the participants ( 30 , 32 , 41 , 74 , 76 , 77 , 80 , 83 ), and in most of the studies between 31% and 91% of the participants identified as White.…”
Section: Resultsmentioning
confidence: 99%
“…About half of the identified studies (41.4%) focused on the implementation and analysis of a variety of AI prediction algorithms for different outcomes in online mental healthcare, including treatment responses and symptom remission, treatment dropouts, and treatment engagement and adherence ( 28 32 , 87 89 , 91 94 ). The identified studies applied ML algorithms such as: DL, and ANN algorithms to process large amounts of treatment data to identify helpful prediction factors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations